دور التقييم الشامل في تحسين جودة تدريس العلوم وتحفيز التلاميذ على التعليم المستمر (Journal of the College of Basic Education, 2025)
This study aimed to analyze the impact of comprehensive assessment on improving the quality of science teaching, by enabling teachers to identify strengths and weaknesses in students' performance, and exploring the role of comprehensive assessment in stimulating continuous learning by providing continuous feedback. The study also addressed the impact of comprehensive assessment on developing students' skills, such as critical and analytical thinking, and its impact on enhancing interaction between teachers and students through continuous dialogue.The study relied on the descriptive analytical approach to analyze the role of comprehensive assessment in improving science teaching and stimulating continuous learning. Data were collected using a questionnaire directed to a sample of science teachers in secondary schools in Baghdad Governorate, Iraq, with the aim of measuring their opinions and experiences related to comprehensive assessment methods. The responses were analyzed using appropriate statistical methods.The study boundaries included "Baghdad International Private School", "International English", and "Distinguished Secondary School", and focused on teachers and students during the 2024 academic year.The study reached several results, most notably that comprehensive assessment plays a major role in motivating students to pursue their education more seriously. The results showed that students who were subjected to comprehensive and continuous assessment showed greater interest in learning and became more engaged in lessons. The implementation of comprehensive assessment also increased positive interaction between teachers and students, allowing students to provide feedback and identify areas for improvement. This led to the development of teaching strategies that were more appropriate to the needs of each student.Furthermore, comprehensive assessment encouraged students to think critically and creatively, as they began to explore scientific materials in new ways and find innovative solutions to scientific problems. The study recommended providing training programs targeting the development of teachers’ skills in using comprehensive assessment strategies effectively, to ensure that they are aligned with students’ needs.